Overtraining is associated with DNA damage in blood and skeletal muscle cells of Swiss mice - Pereira, Bruno Cesar; Pauli, José Rodrigo [UNESP]; Antunes, Lusânia Maria Greggi; De Freitas, Ellen Cristini; De Almeida, Mara Ribeiro; De Paula Venâncio, Vinícius; Ropelle, Eduardo Rochete; De Souza, Claudio Teodoro; Cintra, Dennys Esper; Papoti, Marcelo; Da Silva, Adelino Sanchez Ramos (Springer Nature, 2013)
Background: The alkaline version of the single-cell gel (comet) assay is a useful method for quantifying DNA damage. Although some studies on chronic and acute effects of exercise on DNA damage measured by the comet assay have been performed, it is unknown if an aerobic training protocol with intensity, volume, and load clearly defined will improve performance without leading to peripheral blood cell DNA damage. In addition, the effects of overtraining on DNA damage are unknown. Therefore, this study aimed to examine the effects of aerobic training and overtraining on DNA damage in peripheral blood and skeletal muscle cells in Swiss mice. To examine possible changes in these parameters with oxidative stress, we measured reduced glutathione (GSH) levels in total blood, and GSH levels and lipid peroxidation in muscle samples. Results: Performance evaluations (i.e., incremental load and exhaustive tests) showed significant intra and inter-group differences. The overtrained (OTR) group showed a significant increase in the percentage of DNA in the tail compared with the control (C) and trained (TR) groups. GSH levels were significantly lower in the OTR group than in the C and TR groups. The OTR group had significantly higher lipid peroxidation levels compared with the C and TR groups. Conclusions: Aerobic and anaerobic performance parameters can be improved in training at maximal lactate steady state during 8 weeks without leading to DNA damage in peripheral blood and skeletal muscle cells or to oxidative stress in skeletal muscle cells. However, overtraining induced by downhill running training sessions is associated with DNA damage in peripheral blood and skeletal muscle cells, and with oxidative stress in skeletal muscle cells and total blood. © 2013 Pereira et al.; licensee BioMed Central Ltd.
Keywords: Aerobic training; DNA damage; Overtraining; Oxidative stress